One, two, buckle my shoe - Christie, Agatha, 1890-1976. (New York : Berkley, 1984)
Hercule Poirot doesn't believe the amiable old dentist shot himself. He has too many clues and a killer who is not satisified with one victim.
"A Hercule Poirot mystery.".
Also published as An overdose of death, and, The patriotic murders.
Young Adult
Keywords: Murder -- Fiction; Poirot, Hercule (Fictitious character) -- Fiction; Homicide -- Fiction; Mystery fiction; Poirot, Hercule (Fictional character) -- Fiction